EFFECT OF DOSAGE AND INTERVAL OF GLYPHOSATE AND OXYFLUORPHEN HERBICIDE ON THE GROWTH AND RESULTS OF SOYBEAN (Glicyne max L. Merr) - Sholihul A’mal (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
This study aims to study and determine the effect of the application of glyphosate and oxyfluorfen to suppress weed growth on soybean plantations with different application doses and time intervals. The research was conducted in February - May 2009 in Jatikerto Village, Malang. This research was designed using a randomized design. factorial group (RAK) factorial, two treatment factors with 3 replications: Factor I (percentage of herbicide doses) P1: 25% glyphosate herbicide + 75% oxyfluorfen herbicide, P2: 50% glyphosate herbicide + 50% oxyfluorfen herbicide, P3: 75 % glyphosate herbicide + 25% oxyfluorfen herbicide. Factor II (application time interval): H1: glyphosate and oxyfluorfen mixed, H2: oxyfluorfen herbicide spraying followed by glyphosate herbicide without time interval, H3: spraying oxyfluorfen herbicide one day later followed by glyphosate herbicide. Observation of weeds was carried out by means of vegetation analysis at the age of 0, 14, 28, 42, 56 days after spraying. The experimental results showed that the percentage of glyphosate + oxyfluorfen herbicide doses and the time interval of spraying had an effect on the variables of plant height, number of leaves, leaf area and total plant dry weight. The combined treatment of 25% gifphosphate herbicide + 75% oxyfluorfen by mixing the two types of herbicides resulted in better plant growth results when compared to other combination treatments. The effect of the treatment on crop yield/land area showed that the percentage dose treatment had no significant effect on yield/plant variables, but the day interval treatment in the herbicide mixing treatment (H1) was able to increase the yield/plant 24,983% from the one day interval treatment. Mixing two types of glyphosate and oxyfluorfen herbicides with various dosage percentages was able to increase the growth and yield of soybean plants.